2017
DOI: 10.1371/journal.pone.0172555
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent inhibition of mTORC1 and mTORC2 by WYE-687 inhibits renal cell carcinoma cell growth in vitro and in vivo

Abstract: Mammalian target of rapamycin (mTOR)in renal cell carcinoma (RCC) represents a valuable oncotarget for treatment. We here tested the potential anti-RCC activity by a novel mTOR kinase inhibitor WYE-687in vitro and in vivo.WYE-687 was cytotoxic and anti-proliferative to established RCC cell lines (786-O and A498) and primary human RCC cells. Yet, it was non-cytotoxic toHK-2 tubular epithelial cells.WYE-687 provoked caspase-dependent apoptosis in the RCC cells. At the molecular level, WYE-687 almost completely b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…in vivo and in vitro observation showed that blocking mTOR1 and mTORC2 activation results in prevention of tumor progression in TSC +/− mice. In accordance with our data, similar recent findings show that new mTOR kinase inhibitor (WYE-687) increased apoptosis and blocked activation of both mTORC1 and mTORC2 through the feedback activation of p-Akt in renal cancer cells as well as the oral administration of WYE-687 potently suppressed tumor growth in nude mice injected with renal cancer cells [ 33 ]. These findings suggest that suppressing the HIF-2 may be an important therapeutic strategy for the treatment of tumorigenesis in TSC patients.…”
Section: Discussionsupporting
confidence: 92%
“…in vivo and in vitro observation showed that blocking mTOR1 and mTORC2 activation results in prevention of tumor progression in TSC +/− mice. In accordance with our data, similar recent findings show that new mTOR kinase inhibitor (WYE-687) increased apoptosis and blocked activation of both mTORC1 and mTORC2 through the feedback activation of p-Akt in renal cancer cells as well as the oral administration of WYE-687 potently suppressed tumor growth in nude mice injected with renal cancer cells [ 33 ]. These findings suggest that suppressing the HIF-2 may be an important therapeutic strategy for the treatment of tumorigenesis in TSC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Cells were obtained by rinsing and filtering. Primary ccRCC cells were cultured in FBS-DMEM/F12 medium supplemented with 10 ng/mL basic fibroblast growth factor (bFGF) and 10 ng/mL epidermal growth factor (EGF) [32] . After 3 to 6 passages, primary ccRCC cells were used in our study.…”
Section: Primary Culture Of Human Rcc Cellsmentioning
confidence: 99%
“…Our in vivo and in vitro findings showed that blocking mTOR and activating AMPK prevented tumor progression in a tumor xenograft mouse model. In agreement with our findings, it was recently reported that a new mTOR kinase inhibitor, WYE‐687, increased apoptosis and blocked activation of both mTORC1 and mTORC2 through the feedback activation of p‐Akt in RCC cells, and oral administration of WYE‐687 potently suppressed tumor growth in nude mice injected with 786‐O cells (Pan et al ., ). Induction of VEGF expression is dependent on HIF‐mTOR activation, which indicates a critical function of the HIF‐mTOR pathway in regulating angiogenesis (Land and Tee, ).…”
Section: Discussionmentioning
confidence: 97%
“…Activation of the Akt/mTOR signaling pathway positively regulates HIF (Woo et al, 2015), making mTOR inhibitors attractive anticancer agents. The use of mTOR inhibitors in the treatment of various types of cancer has been actively studied both preclinically and clinically (Jacinto et al, 2004;Mayer and Grummt, 2006;Pan et al, 2017;Sarbassov et al, 2006). On the other hand, AMP kinase (AMPK) is the primary energy sensor in cells that activates tumor suppressor genes to block HIF activity (Tong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%